Publication rates of hematology/oncology abstracts presented at major pharmacy association meetings. (April 2022) - Wooten, Kiley M; Arnall, Justin R; Bowser, Kiarra M; J Pennell, Laurie; Wade-Davis, Jazmin N; Olin, Jacqueline L; Taylor, Margaret; Moore, Donald C
Introduction: Professional conferences are where research findings are initially presented. Studies suggest many research ideas presented at conferences are never published. Previous studies have demonstrated that the full publication rate of abstracts presented at pharmacy meetings is approximately 20%. The objective of this study was to determine the full publication rate of hematology/oncology abstracts presented at major pharmacy organization annual meetings. Methods: A systematic search of PubMed and Google Scholar was performed. Publication status was evaluated for hematology/oncology abstracts presented at annual meetings for the following organizations: American College of Clinical Pharmacy Annual Meeting, American Society of Health-System Pharmacists Midyear Clinical Meeting, Hematology/Oncology Pharmacy Association Annual Meeting, and International Society of Oncology Pharmacy Practitioners Annual Meeting. Data collected included the meeting of abstract presentation, number of authors, abstract study type, country of origin, journal of publication, and type of publication. Abstracts presented as trainee research were excluded. Results: Of 451 oncology abstracts evaluated, the most common topic categories included pharmacotherapy (n = 244; 54.1%), clinical pharmacy practice (n = 84; 18.6%), and operational/compounding (n = 69; 15.3%). The overall publication rate was 17.5% (n = 79). Abstracts were published as full manuscripts over a spread of 48 different journals. Factors associated with full publication included abstracts with more than 5 authors (OR 3.86, 95% CI 2.32-6.43; p < 0.0001) and abstracts presented at oncology-focused pharmacy meetings (OR 2.92, 95% CI 1.49-5.72; p = 0.0018). Conclusion: This study showed an overall publication rate of 17.5% for abstracts presented at pharmacy meetings, consistent with prior studies.